The Appropriate Combination of Hemagglutinin and Neuraminidase Prompts the Predominant H5N6 Highly Pathogenic Avian Influenza Virus in Birds - Wang, Xiuhui; Zeng, Zhaoyong; Zhang, Zaoyue; Zheng, Yi; Li, Bo; Su, Guanming; Li, Huanan; Huang, Lihong; Qi, Wenbao; Liao, Ming (Frontiers in Microbiology, 2018)
Haemagglutinin (HA) and neuraminidase (NA) are two vital surface glycoproteins of influenza virus. The HA of H5N6 highly pathogenic avian influenza virus is divided into Major/H5 and Minor/H5, and its NA consists of short stalk NA and full-length stalk NA. The strain combined with Major/H5 and short stalk NA account for 76.8% of all strains, and the proportion was 23.0% matched by Minor/H5 and full-length stalk NA. Our objective was to investigate the influence of HA–NA matching on the biological characteristics and the effects of the epidemic trend of H5N6 on mice and chickens. Four different strains combined with two HAs and two NAs of the represented H5N6 viruses with the fixed six internal segments were rescued and analyzed. Plaque formation, NA activity of infectious particles, and virus growth curve assays, as well as a saliva acid receptor experiment, with mice and chickens were performed. We found that all the strains can replicate well on Madin–Darby canine kidney (MDCK) cells and chicken embryo fibroblasts (CEF) cells, simultaneously, mice and infection group chickens were complete lethal. However, the strain combined with Major/H5 and short stalk N6 formed smaller plaque on MDCK, showed a moderate replication ability in both MDCK and CEF, and exhibited a higher survival rate among the contact group of chickens. Conversely, strains with opposite biological characters which combined with Minor/H5 and short stalk N6 seldom exist in nature. Hence, we drew the conclusion that the appropriate combination of Major/H5 and short stalk N6 occur widely in nature with appropriate biological characteristics for the proliferation and transmission, whereas other combinations of HA and NA had a low proportion and even have not yet been detected.